2019
DOI: 10.1155/2019/9027803
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Brain State Transition Process of Dynamic Function Connectivity Based on Resting State fMRI

Abstract: BOLD-fMRI technology provides a good foundation for the research of human brain dynamic functional connectivity and brain state analysis. However, due to the complexity of brain function connectivity and the high dimensionality expression of brain dynamic attributions, more research studies are focusing on tracking the time-varying characteristics through the transition between different brain states. The transition process is considered to occur instantaneously at some special time point in the above research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
4
4
0
Order By: Relevance
“…Also, the process of association and dissociation within DMN components is also revealed by Allen et al ) where brain states were described using K-means clustering. More importantly, several studies also showed that the dynamic states transition leads to the inclusion of some FPN regions in the DMN in some brain states Liu et al, 2019), which was also obtained in our study (results of dataset 1). Similarly, the temporal network alternates its reconfiguration between left, right and complete modules.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Also, the process of association and dissociation within DMN components is also revealed by Allen et al ) where brain states were described using K-means clustering. More importantly, several studies also showed that the dynamic states transition leads to the inclusion of some FPN regions in the DMN in some brain states Liu et al, 2019), which was also obtained in our study (results of dataset 1). Similarly, the temporal network alternates its reconfiguration between left, right and complete modules.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, DAN expands dynamically its network to include the visual components. The dynamic inclusion of these networks echoes the presence of high correlation between them, which was supported in previous studies Liu et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The investigation of functional brain network connectivity (FNC) as a time-varying property in resting state functional magnetic resonance imaging (rs-fMRI) studies began relatively recently and, to date, has remained primarily concerned with capturing a handful of discrete static states that characterize connectivity as measured on a timescale shorter than that of the full scan ( Allen et al, 2014 ; Damaraju et al, 2014 ; Ou et al, 2015 ; Yaesoubi et al, 2015 , 2017 ; Abrol et al, 2017a , b ; Marusak et al, 2017 ; Barber et al, 2018 ; Diez-Cirarda et al, 2018 ; Faghiri et al, 2018 ; Patanaik et al, 2018 ; Rashid et al, 2018 ; Smith et al, 2018 ; Vergara et al, 2018 ; Xie et al, 2018 , 2019 ; Denkova et al, 2019 ; Espinoza et al, 2019a ; Fiorenzato et al, 2019 ; Fu et al, 2019 ; Gonzalez-Castillo et al, 2019 ; Hou et al, 2019 ; Klugah-Brown et al, 2019 ; Li et al, 2019 , 2021 ; Liu et al, 2019 ; Mash et al, 2019 ; Rabany et al, 2019 ; Yao et al, 2019 ; Zhou et al, 2019 ; Agcaoglu et al, 2020 ; d’Ambrosio et al, 2020 ; Mennigen et al, 2020 ; Shappell et al, 2021 ). Temporal variation in fMRI has been employed primarily to establish evidence of stable hemodynamic covariation between pairs of functionally or anatomically defined brain regions or functionally coherent distributed spatial networks.…”
Section: Introductionmentioning
confidence: 99%